Complex Systems Design &Amp; Management 2018
DOI: 10.1007/978-3-030-04209-7_16
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic Design Engineering

Abstract: The Concept Phase of Systems Engineering, also known as Design, is most critical for it determines most of the cost, complexity and value of a system. Given the interdisciplinary nature of Design, it is no wonder that a wide variety of tools and approaches have been developed to aid in addressing design problems. Even within the engineering community, designers from different disciplines working on different types of problems have devised their own frameworks to demystify the design process. This paper describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Design Thinking offers tools for understanding the user, and for processing the knowledge into meaningful need definitions. Watanabe et al (2017), Zhao (2015), Wade et al (2017), Tomita et al (2017), and Shafaat & Kenley (2015) suggested approaches from Design Thinking in order to include the human as a part of the system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Design Thinking offers tools for understanding the user, and for processing the knowledge into meaningful need definitions. Watanabe et al (2017), Zhao (2015), Wade et al (2017), Tomita et al (2017), and Shafaat & Kenley (2015) suggested approaches from Design Thinking in order to include the human as a part of the system.…”
Section: Discussionmentioning
confidence: 99%
“…Wade, Hoffenson, & Gerardo (2017) emphasized that the concept phase of System Engineering, also known as Design in the larger community outside of Systems Engineering, is critical because it determines cost, complexity, and value of a system. Wade et al (2017) compared existing design paradigms for designing complex products: Design Thinking, Systems Thinking, Systemic Design, engineering design, Systems Engineering, agile systems, and software engineering. The proposed framework entitled "Systemic Design Engineering" unifies the strengths of each of these existing paradigms.…”
Section: State Of the Artmentioning
confidence: 99%
“…Previous research has discussed the potential of combining design-and systems approaches [5]- [8]. However, we have not found literature that focuses on the industrial challenges for systems engineers to innovate in a soft systems context, nor the main influencing factors to address for the industry to overcome these challenges.…”
Section: Introductionmentioning
confidence: 94%
“…Wade, Hoffenson, and Gerardo [5] discussed strength and weaknesses of major paradigms for designing complex systems. Their discussion included design thinking, systems thinking, systemic design, engineering design, and systems engineering.…”
Section: Introductionmentioning
confidence: 99%
“…The systems engineering community has recently begun to adopt design thinking, and it is starting to be taught in systems engineering programs. Also, some have proposed integrating design thinking into the systems engineering process, including Sirietta Simoncini of Cornell University (Simoncini, 2015) and Jon Wade of the Stevens Institute of Technology (Wade, 2017). For a subjective toolbox, to bring an increased emphasis on design, the following heuristic is proposed: to integrate systems thinking with design thinking.…”
Section: Designmentioning
confidence: 99%